Thyroid disruption in the lizard Podarcis bocagei exposed to a mixture of herbicides: a field study - Bicho, Rita C. (2014)
Pesticide exposure has been related with thyroid disrupting effects in different vertebrate species. However, very little is known about the effects of these compounds in reptiles. In the Mediterranean area, lacertid lizards are the most abundant vertebrate group in agroecosystems, and have been identified as potential model species for reptile ecotoxicology. The aim of this study was to understand if the herbicides applied in corn fields have thyroid disruptive effects in the lizard Podarcis bocagei. Adult male lizards were captured in north-western Portugal in corn fields treated with herbicides (exposed sites), and in organic agricultural fields (reference sites). Thyroid and male gonad morphology and functionality, and testosterone levels were investigated through histological, immunohistochemical and biochemical techniques. Lizards from exposed locations displayed thyroid follicular lumens with more reabsorption vacuoles and significantly larger follicular area than those from reference fields. Furthermore, testes of lizards from exposed locations had significantly larger seminiferous tubule diameters, significantly higher number of spermatogenic layers and displayed an upregulation of thyroid hormone receptors when compared with lizards from reference areas. These findings strongly suggest that the complex mixture of herbicides that lizards are exposed to in agricultural areas have thyroid disrupting effects which ultimately affect the male reproductive system. Alachlor, which has demonstrated thyroid effects in mammals, may be largely responsible for the observed effects.